Криза чверті життя - Сабадаш, В. О. (ХНУРЕ, 2021)
Nowadays, with the development of technologies and sciences, various areas and branches of professions arise, and a young person, due to a lack of knowledge and understanding, is difficult to decide what he wants to do and which way to go. Associated with this is fear of decision making and uncertainty in choice. Which leads to the onset of a disorder that can be characterized as a quarter-life crisis. This is a crisis that can be experienced at the age of twenty, when there is contact with the "real world" associated with anxiety about the direction and quality of your life, which is caused by the stress of becoming an adult. Research has shown that unemployment and career choices are common causes of anxiety or stress in young people.
Keywords: філософія; криза чверті життя